1995
DOI: 10.1038/bjc.1995.540
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for extensive lymphadenectomy in early gastric carcinoma

Abstract: Summary The incidence of nodal metastasis in early gastric carcinoma (EGC) is 10-20%. However, the optimal nodal dissection for early gastric carcinoma has not been established. A retrospective study was conducted in 392 consecutive patients who underwent potentially curative distal gastrectomy for EGC between 1962 and 1990. Of these 295 patients treated after September 1972 were prospectively entered into an extensive lymphadenectomy protocol. These patients were compared with 97 patients with simple gastrect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 33 publications
(36 reference statements)
1
37
0
1
Order By: Relevance
“…Similar results were reported by other authors (25,36,37). Although Japanese surgeons routinely perform extended lymphadenectomy for gastric cancer patients without distant metastasis, many western investigators have reported that D2 or more extended lymphadenectomy could not improve the prognosis of gastric cancer significantly compared with D1 lymphadenectomy, which is generally accepted by surgeons in western countries (38)(39)(40)(41)(42)(43). Nevertheless, other investigators have stated that D2 lymph node dissection might improve the survival of patients with lymph node-negative gastric carcinoma (25,44,45).…”
Section: Discussionmentioning
confidence: 97%
“…Similar results were reported by other authors (25,36,37). Although Japanese surgeons routinely perform extended lymphadenectomy for gastric cancer patients without distant metastasis, many western investigators have reported that D2 or more extended lymphadenectomy could not improve the prognosis of gastric cancer significantly compared with D1 lymphadenectomy, which is generally accepted by surgeons in western countries (38)(39)(40)(41)(42)(43). Nevertheless, other investigators have stated that D2 lymph node dissection might improve the survival of patients with lymph node-negative gastric carcinoma (25,44,45).…”
Section: Discussionmentioning
confidence: 97%
“…Some reports showed that lymph node dissection improved the survival of patients with histologically node-negative EGC [21, 101]. Although some studies criticize local resection and limited lymph node dissection in EGC [10, 102], clinical implications of micrometastasis in the lymph nodes are unclear, and prognostic significance of systematic lymph node dissection for histologically node-negative EGC are controversial.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…This is the reason why systematic dissection of the regional lymph nodes is recommended and prophylactic dissection is mandatory for the surgical treatment of gastric cancer [9, 10, 20, 21]. However, lymph node metastasis is rare in patients with mucosal cancer, and is mostly restricted to the perigastric nodes in patients with node-positive EGC [22, 23, 24, 25, 26].…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the series reported by Kodera et al [25], of 271 EGCs, 84 (31%) were multiple. In other series, the rate of multifocal lesions was 9% (95% CI, 8%-10%) in six accumulated series [4,6,7,12,19,26]. The possibility of missing multiple foci, with increased risk of gastric remnant relapse, has been used as a rationale for routine total gastrectomy [7,15].…”
Section: Multifocal Carcinomamentioning
confidence: 99%